2018
DOI: 10.1002/adfm.201804943
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Collagen‐Based Biomaterials for Regenerative Biomedicine

Abstract: In recent decades, collagen is one of the most versatile biomaterials used in biomedical applications, mostly due to its biomimetic and structural composition in the extracellular matrix (ECM). Several attempts are proposed for designing innovative collagen-based biomaterials and applying them in tissue regeneration. The regeneration of different tissues is prompted by different types and diverse physical forms of collagen-based biomaterials prepared by various methods. Based on such concepts, the source, stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
197
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(209 citation statements)
references
References 197 publications
0
197
0
12
Order By: Relevance
“…The XRD spectrum of PPY/Coll and PPY/Coll/n-Sr@BG appear in Figure 1(b). As can be seen, the PPY/Coll composite display wide planes at two-theta ¼ 24, which might be because of the undefined idea of collagen particles [19]. Similarly, the PPY/Coll/n-Sr@BG (demonstrates a wide planes at two-theta ¼ 24) [32].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The XRD spectrum of PPY/Coll and PPY/Coll/n-Sr@BG appear in Figure 1(b). As can be seen, the PPY/Coll composite display wide planes at two-theta ¼ 24, which might be because of the undefined idea of collagen particles [19]. Similarly, the PPY/Coll/n-Sr@BG (demonstrates a wide planes at two-theta ¼ 24) [32].…”
Section: Resultsmentioning
confidence: 92%
“…The reason for this examination was to explore a conceivable dealing for fixing harmed nerves and to beat the present weaknesses polypyrrole has in tissue building. Collagen (Coll) is broadly utilized in nerve tissue building because of its great viability, non-biodegradable, and tensile strength [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The direct usage of abrasives also requires substrates to be rigid and having enough thickness, which may not be suitable for thin films the extensively applied materials for tissue-engineering vascular grafts. Directional top-down freezing [59,60] and self-forming via ion beam [61] are also capable of fabricating anisotropic biomaterials. However, these methods are less reported for vascular tissue engineering and still waiting for further development to have effective cell alignment.…”
Section: Other Fabrication Methods For Engineering Biomaterials With mentioning
confidence: 99%
“…The skin and cartilage of the blue shark are rich in types I and II collagen, respectively (Nomura, 2001). Meanwhile, type I collagen is the most commonly used and researched collagen (Lin et al, 2019). Recent studies have shown that sharkskin collagen is useful as the material for cell culture matrix, a substrate for matrix metalloprotease involved in tissue metabolism (Nomura, 2001), wound dressings, vitreous implants and carrier for drug delivery (Senaratne, Park and Kim, 2006).…”
Section: Shahidi Et Almentioning
confidence: 99%
“…Recent studies have shown that sharkskin collagen is useful as the material for cell culture matrix, a substrate for matrix metalloprotease involved in tissue metabolism (Nomura, 2001), wound dressings, vitreous implants and carrier for drug delivery (Senaratne, Park and Kim, 2006). According to the available database, including Web of Science, there are increasing number of collagen-based biomaterials that are being approved for regenerative medicine applications (Lin et al, 2019). Several studies have reported that collagen from fresh water fish has a lower cytotoxic effect and higher cell viability than bovine collagen (Song et al, 2006;Lin et al, 2019).…”
Section: Shahidi Et Almentioning
confidence: 99%